The Global Community yearbook of international law and jurisprudene 2017 - Ziccardi Capaldo, Giuliana; Global Community (New York, NY : Oxford University Press, 2018)
The 2017 edition both updates readers on the important work of long-standing international tribunals and introduces readers to more novel topics in international law. The Yearbook has established itself as an authoritative resource for research and guidance on the jurisprudence of both UN-based tribunals and regional courts. The 2017 edition continues to provide expert coverage of the Court of Justice of the European Union and diverse tribunals from the International Court of Justice (ICJ) to criminal tribunals such as the International Criminal Court (ICC) and the Tribunals for the Former Yugoslavia and Rwanda, to economically based tribunals such as ICSID and the WTO Dispute Resolution panel.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 26, 2018).
Keywords: International law -- Periodicals; Jurisprudence -- Periodicals; Law; International law